Insect pests of Kalamansi citrus (Citrofortunella microcarpa) and their symptoms of infestation in Bengkulu, Indonesia - Sempurna Ginting,; Djamilah,; Pryatiningsih, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Kalamansi citrus (Citrofortunella microcarpa) is one of many horticultural commodities cultivated in Bengkulu, Indonesia. Insect pests are organisms that interfere growth and economic value of crops such as citrus. Insect pests on citrus plants result in decreased production ranging from 50%–77% worldwide. Knowledge of types of pest insects and their natural enemies is very important to designing effective control strategies. This study aimed to identify insect pests associated with Kalamansi citrus in Bengkulu. The number of Kalamansi citrus sample plants observed was 20 (selected randomly) and the citrus plants observed were about six years age. The results showed that Kalamansi citrus was infested by four orders and eight families of insects, including Hemiptera: Pentatomidae (Rhynchocoris poseidon Kirk), Hemiptera: Aphididae (Toxoptera citridicus Kirk), Hemiptera: Pseudococcidae (Planococcus citri Risso), Hemiptera: Flatidae (Metcalfa pruinosa (Say), Thysanoptera: Thripidae (Scirtothrips dorsalis Hood), Lepidoptera: Gracillariridae (Phyllocnistis citrella Stainton), Lepidoptera: Papilionidae (Papilio demoleus L.), and Diptera: Tephritidae (Bactrocera spp.). The dominant pests on Kalamansi citrus belonged to the orders Diptera (fruit flies) and Hemiptera. Some insect pests attack oranges and cause direct damage to crops by eating the affected plant parts, whereas others act as vectors for viruses and other pathogens. Some insects eat leaves, flowers, and fruits directly.